Evaluación de dos métodos de destete en terneros de raza holstein mestizos sin registro de dos semanas de edad en la parroquia Eloy Alfaro perteneciente a la provincia de Cotopaxi. - Rueda Flores, William René (2020)
The feeding of the calves during their first months of life is of great importance, since it is here that it depends on the animal to achieve a good replacement in the east for its later sale. The objective of the work was to evaluate the behavior of the study groups in relation to weight gain and dry matter consumption by means of a controlled diet. The records were made daily during the six weeks including the week of adaptation whose data were used only to obtain live weight. The first part was the acquisition of 12 calves, which were purchased from different farms in Mejia County, between 5 and 7 days old, for their subsequent transfer to the Eloy Alfaro parish in Cotopaxi Province, at an altitude of 2934 meters above sea level, coordinates (DMS): S05550,06676 W783849,34364. The initial weights were 35.4 kg as a general average. Since there was no marked variation in weights, the distribution of the study groups T0 and T1 was done following a completely randomized scheme, with each treatment having six repetitions, considering each calf as an experimental unit. As for sanitary management, the same follow-up was given to both groups in order to avoid variations in the data obtained. The results were analyzed using the Minitab statistical program with the Dunnett test, a method used when the number of experimental units is limited. Calves in the treatment group were weaned 42 days after the start of the experiment, at which time data collection was completed despite the fact that the comparison group remained on a dairy diet with low dry matter intake. The most representative results are observed during week 5, with a 95% confidence interval for the Control group we have an average of 6433g/7d with a standard deviation of 862g (Lim. Inf 5330 Lim. Sup 7536), also with a 95% confidence interval for the Treatment group we have an average of 8367g/7d with a standard deviation of 1483g (Lim. Inf 7264 Lim. Sup 9470); these results regarding GMDPV.